PENGGUNAAN APLIKASI PERPUSTAKAAN DIGITAL “PERPUSDA WONOSOBO” DAN SOSIALISASI PERPUSTAKAAN DI RADIO SELAMA PANDEMI - Damaris, Betarum; ., Sukaesih; Rukmana, Evi Nursanti; CMS, Samson (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Pandemic conditions, which require people to limit their space, have increased their need for information. This pandemic has also had a major impact on libraries. The most pronounced impact is the service that is not optimal because there are rarely visitors and savings so that it only serves borrowing and book services. This pandemic also makes regional libraries a digital library application and provides education about libraries via radio. This study aims to examine the library during the pandemic, how the benefits of using the digital library application “Perpusda Wonosobo”, and the analysis of having radio mass media in providing educational information about the library. This research uses the descriptive qualitative method. How to obtain data is structured interviews and observations. Researchers see what, where, and how the subject will be extracted information. The results of this study indicate that marketing through promotion makes the use of the digital library application “Perpusda Wonosobo” statistically increased during the pandemic. More and more people are using this digital library application to meet their information needs without having to interfere with the mobility of life during a pandemic. The use of radio media is also an effective secret to introduce to the general public about libraries and education from the library itself. Strong radio makes educational broadcasts more attractive and can reach the public. Furthermore, from this study, more and more people are using digital library applications because they are available in access and use. In the use of radio, information about the library can reach rural areas so that listeners from various backgrounds can listen to it because it is delivered in a language that is easily recognized. Introduction to libraries can also reach areas that have difficulty accessing the internet.